2004
DOI: 10.3149/jms.1301.107
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks of Aging Gay Men

Abstract: Social support becomes an increasingly important resource for people as they age. Research has shown that the needs of older gay men are no different than those of their heterosexual counterparts, nor are older gay men more isolated than older men in general. Research has shown gay men rely on friendship networks more often than on family while heterosexual men rely more on family for social support. Using the most conservative estimates, there are more than two million gay men over the age of 60 in the United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
3
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 9 publications
6
78
3
4
Order By: Relevance
“…It was reported that this meant that some did not have appropriate people to appoint as substitute decision makers. The extent of older gay men's social connections has been widely debated in the GLBT ageing literature (Hughes 2009;Shippy et al 2004), and there remains mixed findings from research as to the extent to which older gay men may be isolated. Previous researchers have identified that even though they may be more likely to live alone than heterosexual men and lesbians, some older gay men are intimately involved in self-made communities and support networks (Heaphy 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that this meant that some did not have appropriate people to appoint as substitute decision makers. The extent of older gay men's social connections has been widely debated in the GLBT ageing literature (Hughes 2009;Shippy et al 2004), and there remains mixed findings from research as to the extent to which older gay men may be isolated. Previous researchers have identified that even though they may be more likely to live alone than heterosexual men and lesbians, some older gay men are intimately involved in self-made communities and support networks (Heaphy 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Lyons et al (2012) found that 30% of gay men aged 40-49 lived alone, 38% aged 50-59 lived alone, and 44% of gay men aged 60 and older lived alone. Other research has indicated that 65.8% of gay men aged 50-82 years lived alone (Shippy et al, 2004). In addition, older gay men (40.66%) are more likely to live alone than older heterosexual men (15.15%; Fredriksen-Goldsen et al, 2013).…”
mentioning
confidence: 98%
“…Selon les études disponibles, provenant principalement des États-Unis, la majorité des aînés gais et lesbiennes ont une bonne santé mentale (D'Augelli, Grossman, Hershberger et O'Connell, 2001 ;FredriksenGoldsen et al, 2011 ;Jessup et Dibble, 2012 ;Lévy et al, 2012 ;Lyons, Pitts et Grierson, 2013 ;McCann, Sharek, Higgins, Sheerin et Glacken, 2013 ;Orel, 2004 ;Shippy, Cantor et Brennan, 2004 Par ailleurs, des études portant sur des populations d'âge varié constatent que les personnes GLB sont plus à risque de développer des problèmes de santé mentale que la population hétérosexuelle en général (Addis et al, 2009 ;Fredriksen-Goldsen, Kim, Barkan, Muraco et HoyEllis, 2013 ;Meyer, 2003). King et al (2008) concluent de leur revue systématique et de leur méta-analyse d'études portant sur la santé mentale des personnes GLB en comparaison des personnes hétéro-sexuelles (cohortes, cas témoins ou études transversales) que les risques de dépression, de troubles d'anxiété, de dépendance à l'alcool et à d'autres substances sont 1,5 fois plus élevés dans la population GLB comparativement à la population hétérosexuelle (tous âges confondus), alors que le risque de tentative de suicide est deux fois plus élevé.…”
Section: La Santé Mentale Des Aînés Gais Et Lesbiennes : Que Sait-on ?unclassified
“…Le sentiment de solitude et les symptômes dépressifs seraient égale-o 3 ment associés au fait d'avoir vécu des expériences de victimisation antérieurement Jenkins Morales et al, 2014). Il faut rappeler que les gais et les lesbiennes vieillissants sont plus nombreux à vivre seuls que les hommes et les femmes hétérosexuels (Addis et al, 2009), qu'un grand nombre n'ont pas eu d'enfants et qu'un réseau de soutien social restreint pourrait augmenter leur risque de vivre de la solitude et de l'isolement social (Shippy et al, 2004). En somme, concluent Fredriksen-Goldsen et Muraco (2010) dans leur recension de la documentation scientifique, la solitude, une faible estime de soi, l'homophobie intériorisée et la victimisation -passée, actuelle ou anticipée -en raison de l'orientation sexuelle sont des prédicteurs d'une santé mentale fragile.…”
Section: Les Facteurs Affectant Négativement La Santé Mentaleunclassified
See 1 more Smart Citation